PERAN GURU PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN DALAM UPAYA PEMBENTUKAN KARAKTER PESERTA DIDIK - Sukur (Pendidikan Matematika | STKIP YM Bangko, 2021)
About the establishment of national character through character education implemented by the schools is one of the mission of realizing the vision of the Indonesian nation. Which the democratic national education and quality to strengthen noble character, creative, innovative, national paradigm, intelligent, healthy, disciplined and responsible, skilled and master of science and technology. However from the result research and interviews are still occur juvenile delinquency that exceeds normal limits. If less control of their so deviation of violence like this is what happens at school. Negative influence this also arises because the lack of attention their family. This study aims to determine the extent of the role of education Pancasila and citizenship in the efforts to establishment character of students. In Order To seek information by interviewing the teachers and some school students researchers also observe.